Behavioral and Electrophysiological Indices of Memory in Typically Developing and Hypoxic‐Ischemic Injured Infants. (16th September 2013) - Norwood, Agatha; Wagner, Jennifer B.; Motley, Christine; Hirch, Suzanna B.; Vogel‐Farley, Vanessa K.; Nelson, Charles A.
<x xml:space="preserve">Abstract</x> Behavioral and electrophysiological indices of memory were examined in 12‐month‐old typically developing control infants (CON) and infants with history of perinatal hypoxic‐ischemic injury (HII) across 2 days. Using a visual paired comparison (VPC) procedure, novelty preference was tested immediately after a familiarization period and then after delays of 2 min and 24 h. Both groups showed a significant novelty preference only for the no‐delay condition. On day two, event‐related potentials (ERPs) were recorded while infants viewed the VPC familiar face, a more recently familiarized face, and a novel face, and mean amplitude for components thought to reflect memory (positive slow wave, PSW) and attention (negative central, Nc) were computed. In temporal regions, HII showed a diminished Nc and enhanced PSW to the recently familiarized face, while CON showed a similar trend for the PSW only. Overall, infants showed the largest PSW over left scalp regions. Finally, a positive correlation between VPC novelty preference after 24 h and PSW was found in CON, and preliminary results suggest that this association differs as a function of group. Therefore, in comparison with CON, HII showed both similarities and differences on individual tasks of memory as well as potentially disparate relations between the behavioral and neural mechanisms underlying memory performance.